Barriers to access to hepatitis C treatment with direct-acting antivirals in people who inject drugs in the community setting - Elena Yela; Neus Solé; Lidia Puig; Darío López Gallegos; Rafael Clua-García (BMC, 2024)
Abstract Barriers to access to hepatitis C treatment with direct-acting antivirals in people who inject drugs in the community setting. Qualitative study with prison population. Hepatitis C (HCV) treatments with direct-acting antiviral therapy (DAA) are an easy and effective option among people who inject drugs (PWID). However, difficulties in accessing and monitoring treatment in community services and dropouts on release from prison are detected among PWID. For this reason, the aim of the study is to know the access barriers in the diagnosis and treatment of HCV in community health services. An exploratory qualitative study was carried out through semi-structured interviews with 33 PWID recruited in a pre-trial detention prison in Barcelona. The information obtained was analysed using grounded theory. Among PWID sub-population entering prison, personal barriers are related to intense drug use, lack of interest and ignorance of HCV infection and treatment, as well as being in a situation of social exclusion. In relation to health providers, they reported receiving little information, the existence of language barriers in migrants, not receiving screening and treatment proposals, and having poor interactions with some professionals. Systemic barriers were expressed related to the health system circuit being complicated, perceiving little comprehensive care and lack of community support. It is recommended to intensify prevention and treatment campaigns, promoting drug substitution programmes than current ones, improve health education, make the diagnosis and treatment process more flexible, and promote social policies and holistic care for greater coverage of the needs of PWID.